2008
DOI: 10.1074/jbc.m800640200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-1 and Metal Transcription Factor-1 Synergistically Activate the Mouse Metallothionein-1 Gene in Response to Metal Ions

Abstract: Metal activation of metallothionein (MT) gene transcription is dependent on the presence of metal regulatory elements (MREs), which are present in five non-identical copies (MREa through MREe) in the promoter of the mouse MT-1 gene and on the capacity of metal transcription factor-1 (MTF-1) to bind to the MREs in the presence of zinc. We detected a protein, distinct from MTF-1, specifically binding to the MREc region. DNA binding competition experiments using synthetic oligonucleotides and specific anti-NF1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
(98 reference statements)
0
27
1
Order By: Relevance
“…When zinc is present, MTF-1 binds to DNA motifs such as metal response elements (MREs) in the promoter region of MT genes and increases the transcription of MT505152. NFI-C is known to bind to overlapping regions of MRE sites53. During the early odontoblast differentiation period, adequate amount of zinc promotes nuclear translocation of MTF-1 and phosphorylation of SMAD2/3 in the cytoplasm in a dose dependent manner.…”
Section: Function Of Nfic In Dentinogenesismentioning
confidence: 99%
“…When zinc is present, MTF-1 binds to DNA motifs such as metal response elements (MREs) in the promoter region of MT genes and increases the transcription of MT505152. NFI-C is known to bind to overlapping regions of MRE sites53. During the early odontoblast differentiation period, adequate amount of zinc promotes nuclear translocation of MTF-1 and phosphorylation of SMAD2/3 in the cytoplasm in a dose dependent manner.…”
Section: Function Of Nfic In Dentinogenesismentioning
confidence: 99%
“…Sonication was optimized to yield 600 -1000 bp of sheared DNA in chromatin samples from 5 ϫ 10 7 cells/ml of ChIP buffer, and 50 l containing (15 g of DNA) was used for immunoprecipitation with specific preimmune IgG (PI) antibodies. Briefly, after overnight incubation with IgGs ϩ protein G magnetic beads, samples were washed once with 1 ml of low salt ChIP buffer, once with 0.5 M NaCl containing high salt ChIP buffer, followed by 1 ml of LiCl/detergent buffer (28,29). Finally, the beads were washed with 500 l of TE and resuspended in 8 l of 5 M NaCl to reverse crosslinking, and samples were incubated overnight at 65°C in a water bath.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, mouse MTF-1 was found to form a zinc-induced complex with the transcription factor Sp1 and the histone acetyltransferase p300 co-activator [37]. In another study, it was suggested that MTF-1 assisted nuclear factor 1 (NF1) with binding to promoter sequences in order to activate gene transcription in a zinc-dependent manner [38].…”
Section: Introductionmentioning
confidence: 99%